Quality of life of patients with Amyotrophic Lateral Sclerosis - Sue Christine Siqueira; Priscila Valverde de Oliveira Vitorino; Cejane Oliveira Martins Prudente; Tainara Sardeiro de Santana; Gleydson Ferreira de Melo (Rev Rene)
Objective: to analyze the scientific evidence that evaluated the quality of life of patients with Amyotrophic Lateral Sclerosis through ALSAQ-40/ALSAQ-5. Methods: this is an integrative review carried out with eight articles in the database, using controlled keywords. Results: the most impaired domains of quality of life were physical mobility and activities of daily living. Patients with bulbar Amyotrophic Lateral Sclerosis, communication and feeding were more impaired. Problems with health care and lack of social support to the caregiver negatively impacted the patient´s quality of life. Emotional stress was correlated with communication, physical mobility and disease progression in patients with breathing and artificial feeding, but it is not directly related to the advances of physical deterioration, but rather how the patient processes the experiences. Conclusion: patients with Amyotrophic Lateral Sclerosis have a poorer quality of life regarding the motor aspect, and lack of caregiver support worsens the patient´s quality of life.